Investigating the relationship between high‐yield bonds and equities and its implications for strategic asset allocation during the Great Recession - Menounos, Georgios; Alexiou, Constantinos; Vogiazas, Sofoklis (Wiley, 2018)
In this paper, we focus on investing in U.S. high‐yield bonds during the period 2007–2013, a period that covers the Great Recession in the aftermath of the global financial crisis of 2007–2008. First, we use the Fama and French three‐factor model to delve into the relationship between the risk‐adjusted returns of high‐yield bonds and equity market risk factors. Second, we gauge the extent to which the risk‐adjusted returns of high‐yield bonds are significantly higher than equity and investment‐grade bonds' risk‐adjusted returns. Third, by using a modified version of the Black–Litterman model, we explore the asset allocation to high‐yield bonds, accounting for investors' risk tolerance. Our findings suggest that equity market risk factors have significant explanatory power for high‐yield bonds' risk‐adjusted returns, whereas the hypothesis of superior returns on high‐yield bonds over investment‐grade corporate bonds and equities cannot be supported. Our key contribution relates to the strategic asset allocation to high‐yield bonds. Our results suggest that the share of high‐yield bonds does not exceed 4.1% of total assets in a global market portfolio over the period 2007–2013. Notably, the share of high‐yield bonds in a simulated portfolio remains relatively small and stable on a risk‐adjusted basis, irrespective of an investor's risk profile or the phase of the business cycle.
Keywords: asset allocation; Black–Litterman model; Fama–French three‐factor model; global financial crisis; high‐yield bonds